(untitled) (Revista Direito em Debate, 2019)
The emergence and strengthening of the Democratic State of Law have imposed, from the constitutional normative substrate, signposts for the individuals’ actions in society, the State Apparatus and its administrators. Endowed with prerogatives, the Public Administration is therefore charged with achieving the collectively relevant and desired results. Considering this scenario, the objective of this work is to analyze the range of the administrative discretion in the face of decision-making demands, particularly the rigor imposed by the contemporary legal hermeneutic theory. Initially, the understanding consolidated in the legal dogmatic about discretion and its aspects of divergence are presented. Then, one exposes the relation between the interpretative activity and the discretionary act, according to the administrative doctrine. Following the systematic study of this legal institute, one examines the different sorts of discretion as well as their potential fragilities. Finally, the critiques of contemporary hermeneutics are thoroughly presented in reason of the fundamental right to a correct or "true" response.